Biofuels as a New Energy Paradigm: the Key Points of Debate after a Decade* (2013)
* This article is part of the doctoral thesis entitled Scenarios of future expansion of biofuels in Colombia: impacts generated by the expansion of oil palm plantations to produce biodiesel.Biofuels are promoted worldwide as an alternative to partially replace fossil fuels. After more than a decade of implementation, important questions have been raised concerning: i) the impacts generated by the change of use and land coverage; ii) the impacts on prices and food production, iii) the impacts on water and the related ecosystem services, and iv) greenhouse gas (GHG) emissions generated by the changes of land use. This article discusses these issues in the current situation of biofuels with emphasis in the tropical countries. Available studies show that despite their small contribution to the world energy matrix, the large-scale expansion of biofuels can generate negative impacts such as increase in the competition for water and land, especially in the vulnerable ecosystem and social structures in tropical countries.